EFFICIENT LOAD BALANCING TECHNIQUES FOR MOBILE FOG NETWORKS IN THE FOG LAYER: A REVIEW - Agber, Selumun; Abdullahi, Mohammed Bashir; Bashir, Sulaimon Adebayo; Ojerinde, Oluwaseun Adeniyi (FUDMA Journal of Sciences, 2025)
The proliferation of Internet of Things (IoT) devices has significantly increased the demand for cloud services, leading to the emergence of Mobile Fog Networks (FogNets) as an effective paradigm for edge processing. This paper reviews efficient load-balancing techniques within the Fog layer, focusing on their ability to handle increasing workloads and ensure optimal resource utilization. A total of forty (40) peer-reviewed articles published between 2020-2025 were systematically reviewed using a descriptive and comparative analysis approach. The findings reveal that heuristic-based, hybrid, and machine learning driven load-balancing methods demonstrate superior performance in terms of response time, energy efficiency, and latency reduction. However, most existing studies rely on simulation-based evaluation and lack real-world deployment validation. The review concludes that future research should emphasize adaptive, context-aware, and energy-efficient load-balancing strategies to enhance real-time service delivery in FogNets.
Keywords: Internet of Things (IoT); Cloud Computing; Fog Networks (FogNets); Load balancing; Fog layer; Mobile Fog Networks; Fog Computing Environments